E-5: KASHMIR DISPUTE: PROSPECTS OF SETTLEMENT (AN ANALYSIS) - Khan, Mamnoon Ahmed (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
Kashmir Dispute is one of the oldest and most complecated issue of the region South Asia. Numerous efforts have been made to dissolve this most miserable and pain staking dillima but still there are no signs for the resolution of this issue. Pakistan and India recognise themselves as the parties of Kashmir Dispute and always tried to resolve it by their means. But they forgot that Kashmiri nation is the most important party in this Dispute. So any decision on Kashmir must include the will and aspirations of Kashmiri People. In my research paper I tried to highlight the options available to resolve this issue. First option is independence. In this option Kashmir should be declared as independent state. Pakistan and India will provide all the assistance needed by Kashmir. The second option is Division. In this option Kashmir will be divided on the basis of Line of Control. The part inside Pakistan goes to Pakistan and the part inside India will go to India. The third option is temporary control of United Nations. In this option Kashmir will be given in the control of UN for any said duration. The final option is Plebiscite. In this option Kashmiri people will be given the right to vote for either to join Pakistan or India or remain independent.